2015
DOI: 10.1128/aem.00883-15
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Structures, and Collagen-Degrading Mechanisms of Bacterial Collagenolytic Proteases

Abstract: Bacterial collagenolytic proteases are important because of their essential role in global collagen degradation and because of their virulence in some human bacterial infections. Bacterial collagenolytic proteases include some metalloproteases of the M9 family from Clostridium or Vibrio strains, some serine proteases distributed in the S1, S8, and S53 families, and members of the U32 family. In recent years, there has been remarkable progress in discovering new bacterial collagenolytic proteases and in investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 97 publications
(102 reference statements)
1
87
0
1
Order By: Relevance
“…S2B). An exception among the class II proteases, this enzyme does not have a C-terminal PKD-like domain and thus cannot hydrolyze casein (28), explaining the lack of casein degradation in our P. damselae subsp. damselae collection.…”
Section: Figmentioning
confidence: 87%
“…S2B). An exception among the class II proteases, this enzyme does not have a C-terminal PKD-like domain and thus cannot hydrolyze casein (28), explaining the lack of casein degradation in our P. damselae subsp. damselae collection.…”
Section: Figmentioning
confidence: 87%
“…It was suggested that these enzymes could contribute to the deterioration of structural integrity in root dentine (Zhang et al . , Duarte et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Collagenases, including metalloproteinases and serine proteases, are important virulence factors in a variety of pathogenic bacteria. It was suggested that these enzymes could contribute to the deterioration of structural integrity in root dentine (Zhang et al 2015, Duarte et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…MMP-12 CAT is a single domain protease, while collagenase I is multidomain [30], and thus MMP-12 CAT is less susceptible to autoproteolysis. MMP-12 exhibited excellent stability over 16 d storage (Figure 5E).…”
Section: Discussionmentioning
confidence: 99%